M.B. Cunningham, Wider than Heaven. Eighth-century Homilies on the Mother of God (Popular Patristics Serie, 35), Crestwood, N.Y., St. Vladimir’s Seminary Press, 2008. ISBN 978-0-88141-326-7 - Panagopoulos, Spyros P. (De Medio Aevo, 2020)
Reseña del libro de M.B. Cunningham, Wider than Heaven. Eighth-century Homilies on the Mother of God (Popular Patristics Serie, 35), Crestwood, N.Y., St. Vladimir’s Seminary Press, 2008. ISBN 978-0-88141-326-7